Physical and Rheological Properties of Egg Albumin Foams Are Affected by Ionic Strength and Basil Seed Gum Supplementation - Saeed Mirarab Razi; Ali Motamedzadegan; Seyed-Ahmad Shahidi; Ali Rashidinejad (International Journal of Chemical Engineering)
In this study, the effect of ionic strength and basil seed gum (BSG) on the foaming properties of egg white albumin (EWA) was studied. The foam was prepared with 1% EWA (w/v) in the presence of different concentrations of sodium chloride (NaCl; 0, 0.5, and 1% w/v) and BSG (0, 0.1, and 0.3% w/v). The results showed that foam density and foam stability of EWA significantly (p<0.05) increased with an increase in BSG concentration (from 0 to 0.3% w/v). On the contrary, an increase in NaCl concentration (from 0 to 1% w/v) increased foam overrun but decreased foam density. Amplitude rheological parameters indicated an improvement in foam structure with increasing NaCl concentration. In addition, an elastic structure was obtained in the case of the foams with the higher concentrations of NaCl. Elastic modulus (G′) was higher than loss modulus (G″) in the frequency range, and there was low frequency dependency in all of the samples. In constant frequency of 1 Hz, tangent (δ) was the lowest in the sample containing 1% NaCl (w/v), but without BSG. There was a decrease in yield stress values with increasing BSG concentration; however, the increase in NaCl concentration led to an increase in yield stress. The highest yield stress (37 Pa) belonged to the sample containing 1% NaCl, but without BSG. Overall, it was found that both NaCl and BSG could substantially improve the rheological and foaming properties (in particular, foam stability) of egg white albumin.